Islamic Consumption Behavior: The Student Lodgers Towards Packaged Food in Aceh (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2025)
Consumption behaviour in Islam must pay attention to halal and tayyib (wholesome). Packaged food for student lodgers is relatively the leading choice. This research observes the influence of halal labelling, religiosity, and price on students' decisions to buy packaged food, and factors that influence students' choices of packaged food products from an Islamic economic perspective. The uniqueness of the research lies in the object of research which are the student lodgers towards packaged food in Aceh. Primary data is used through a mixed-method approach that combines quantitative and qualitative data. The quantitative respondents were 100 respondents taken using the non-probability sampling method and purposive sampling technique, using multiple linear regression. Qualitative is the result of interviews with three respondents who live in dormitories, boarding house, and rental house. Quantitative results show that the variables of the price and religiosity have a positive and significant effect on packaged food purchase decisions. But the halal labelling variable does not have a positive effect on packaged food purchase decisions. The results of qualitative research imply that the student lodgers in choosing packaged food are influenced by: expiration date, price, packaging, product efficiency, advertising, religiosity, and habit factors. Halal labelling is less considered because of the role of the government and ulama (Islamic scholar) to protect the halal food products.